A way to stable, highly emissive fluorubine dyes: tuning the electronic properties of azaderivatives of pentacene by introducing substituted pyrazines - Fleischhauer, Jan (Chemistry - a European journal, 2012)
Pentacene and its derivatives are among the most important examples of π-electron-rich molecules used in organic field effect transistors. The replacement of CH groups by nitrogen atoms opens an elegant way to generate highly electron-deficient molecules, known as oligoazaacenes. We describe the synthesis and spectroscopic properties of two novel derivatives of this family, namely the zwitterionic and quinoidal conjugated forms of dihydro-5,6,7,12,13,14-hexaazapentacene (fluorubine). We outline a powerful strategy to tune the electronic properties of these redox-active azaacenes by the selective introduction of substituted pyrazines. Their acidochromic and solvatochromic behaviour is investigated experimentally and interpreted with the help of theoretical calculations. The simple “exchange” of substituents or protonation is shown to significantly alter the spectroscopic and electronic properties of these remarkably stable π-systems. Their exceptional optical properties, such as high fluorescence quantum yields combined with a redox-active behaviour, make them promising candidates for sensor materials. Additional marked features in the solid state, such as herringbone packing in combination with short π-π distances, will open access to electronic materials.